2014
DOI: 10.1089/dna.2014.2375
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Cell Populations Associated with Acquired Resistance to Cytostatics and Cancer Stem Cell Features: The Role of Mitochondria in Nuclear Encapsulation

Abstract: Until recently, acquired resistance to cytostatics had mostly been attributed to biochemical mechanisms such as decreased intake and/or increased efflux of therapeutics, enhanced DNA repair, and altered activity or deregulation of target proteins. Although these mechanisms have been widely investigated, little is known about membrane barriers responsible for the chemical imperviousness of cell compartments and cellular segregation in cytostatic-treated tumors. In highly heterogeneous cross-resistant and radior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

8
35
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 73 publications
8
35
0
Order By: Relevance
“…Endopolyploidy, multi-nucleation with multiplication of pronuclei and/or polar bodies are seen in pathological human eggs (numerous examples are seen in the pictures from the Advanced Fertility Center of Chicago http://www.advancedfertility.com/abnormal-ivf-egg-pictures.htm). These pictures resemble those of multi-nucleated (“pregnant”) giant tumour cells presented by Diaz-Carballo, et al [51] and Zhang, et al [50]. Interesting changes are observed in giant tumour cells after reaching “the totipotency checkpoint”.…”
supporting
confidence: 71%
See 4 more Smart Citations
“…Endopolyploidy, multi-nucleation with multiplication of pronuclei and/or polar bodies are seen in pathological human eggs (numerous examples are seen in the pictures from the Advanced Fertility Center of Chicago http://www.advancedfertility.com/abnormal-ivf-egg-pictures.htm). These pictures resemble those of multi-nucleated (“pregnant”) giant tumour cells presented by Diaz-Carballo, et al [51] and Zhang, et al [50]. Interesting changes are observed in giant tumour cells after reaching “the totipotency checkpoint”.…”
supporting
confidence: 71%
“…These experiments were performed on tumour cell lines representing almost all cancer types (breast, ovarian, bladder, colon, glioblastoma, fibrosarcoma, osteosarcoma, retinoblastoma, lymphoma). Moreover, it was shown that these giant polyploid tumour cells possessing large subnuclei ultimately bud smaller cells [51] of fibroblastic shape and with markers of epithelial-mesenchymal transition (EMT) [50]. The occurrence of asymmetric mitotic divisions in the late ETC which precede cellularisation and the release of rejuvenated sub-cells was also suggested by us previously [31].…”
mentioning
confidence: 84%
See 3 more Smart Citations